Role of Pulse Oximetry Screening for Detection of Life Threatening Congenital Heart Detects in Newborn - Faeq Salih, Aso; Mohammed Hamawand, Adnan; Abd Aljabbar Sattar, Riyadh (Kurdistan Journal of Applied Research, 2018)
Most ofnewborns with Congenital Heart Defects (CHDs) can be detected by using echocardiography. However, if such defects are not diagnosed in earlier time, therefore a severe hypoxemia, shock, acidosis and death are considered of some potential sequelae. A prospective study from January 2012 to the end of 2013 was performed and 2181 neonates were enrolled in the study. The pulse oximetry screening (POS) for both hands and one foot were obtained within the first 3-6 hours of life, when post ductal saturation was below 90%, it was considered as a positive screening, while when the saturation is between 90-95% and the difference between pre-and post-ductal saturation was more than 3%, the baby was provisionally considered to be screening as a positive then echocardiography is planned. Among 100 positive POS babies, 45 (45%) of them were detected with CHS, 12 (12%) was with a major CHS and 33 (33%) was with a minor CHS. Out of 12 patients with a major CHD 6 of them (50%) were asymptomatic at the time of POS.POS result was a true negative in 2078 patients, a true positive in 45 patients, false negative in 3 patients, and false positive in 55 and 28/55 of the false positive rate with POS had other pathology. The false positive rate with pulse oximetry screening is (55/2081) = 0.26%. Sensitivity, specificity, positive and negative predictive value for POS in detection of major CHD were 80%, 97.29%, 17.9% and 99.80%, respectively. Pulse oximetry screening is significantly improving the detection of life threatening congenital heart disease at an early stage.